1998
DOI: 10.1016/s0168-6496(97)00091-3
|View full text |Cite
|
Sign up to set email alerts
|

Significance of microbial urea turnover in N cycling of three Danish agricultural soils

Abstract: The importance of microbial urea turnover in N cycling was investigated in three agricultural soils by comparison of gross N mineralization determined by the IS N-xr R dilution technique and urea turnover determined by a new IR C-urea tracer technique. Average urea turnover rates were 1.5 to 4.2 Wg N g 3I d 3I indicating that the soil urea pool was turned over every 9 to 30 min. Urea turnover rates were generally lowest in set-aside soil with increasing activities in bulk and rhizosphere soil from a barley fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Urea breakdown is a rapid process mediated by environmental and cell-associated urease enzymes. Turnover times for the entire urea pool to ammonium has been observed on a scale of hours and as quickly as 9-30 min in agricultural soils (Nielsen, Bonde, & Sørensen, 1998). Urease inhibitors present in fertilizer have only been found to last up to 2 wk (Dawar, Zaman, Rowarth, Blennerhassett, & Turnbull, 2010;Gioacchini et al, 2002;International Plant Nutrition Institute, 2010;Upadhyay, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Urea breakdown is a rapid process mediated by environmental and cell-associated urease enzymes. Turnover times for the entire urea pool to ammonium has been observed on a scale of hours and as quickly as 9-30 min in agricultural soils (Nielsen, Bonde, & Sørensen, 1998). Urease inhibitors present in fertilizer have only been found to last up to 2 wk (Dawar, Zaman, Rowarth, Blennerhassett, & Turnbull, 2010;Gioacchini et al, 2002;International Plant Nutrition Institute, 2010;Upadhyay, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Almost all ureases are cytoplasmic and can constitute up to 1% of the cell dry weight in S. pasteurii [113]. However, ureases can also catalyze ureolysis extracellularly, and it has been reported that soil matrix-bound ureases can represent significant players of ureolysis [116].…”
Section: Ureolysismentioning
confidence: 99%
“…Besides the environmental issue, NH3 volatilization is an economic loss because less N remains available for plants, leading to a reduction in yields. The control of urease activity in the soil may be a technique to increase the plant-available N content (Rawluk et al, 2001), because plants can take up urea molecules (Mérigout et al, 2008) and synthesize urease for intracellular N mineralization and organization into amino acids, and generally outcompete microorganisms in the uptake of urea from the soil urea stable pool (Harder Nielsen et al, 1998). Urea with urease inhibitors can be used as side-dress fertilization to decrease urea-derived NH3 formation on the soil surface and foster urea movement to deeper soil layer through water infiltration.…”
Section: Urease Inhibitorsmentioning
confidence: 99%